Role of NMDA receptor GluN2D subunit in the antidepressant effects of enantiomers of ketamine - Soichiro Ide; Yuiko Ikekubo; Masayoshi Mishina; Kenji Hashimoto; Kazutaka Ikeda (Elsevier, 2017)
We investigated the rapid and sustained antidepressant effects of enantiomers of ketamine in N-methyl-d-aspartate (NMDA) receptor GluN2D subunit knockout (GluN2D-KO) mice. Intraperitoneal administration of ketamine or its enantiomers 10 min before the tail-suspension test exerted significant antidepressant effects on restraint stress-induced depression in both wildtype and GluN2D-KO mice. The antidepressant effects of (RS)-ketamine and (S)-ketamine were sustained 96 h after the injection in both wildtype and GluN2D-KO mice, but such sustained antidepressant effects of (R)-ketamine were only observed in wildtype mice. These data suggest that the GluN2D subunit is critical for the sustained antidepressant effects of (R)-ketamine.